Cystodistension injuries and long-term bladder functional outcomes: A unique case series from medical malpractice. (November 2020) - Goldsmith, Louise; Eyre, David; Reynard, John
Objectives: Bladder overdistension injuries are rare, but they can have devastating effects on the individual and lead to litigation. We aimed to (a) test the hypothesis that larger distension volumes and longer distension times are more likely to generate acontractile bladders, (b) determine prognostic information and (c) guide management protocols aimed at preventing cystodistension injuries. Patients and methods: We report 18 cases of cystodistension injury following acute urinary retention. One author provided expert medical opinion in these cases, where redress was sought in the UK courts through medical malpractice claims. Data were collected retrospectively. Results: The cohort comprised 17 females and 1 male. The mean age was 31 years (range 17–69 years). Precipitating events included six surgical procedures, 11 vaginal deliveries and one episode of back pain. The median retention volume was 1450 mL (range 1000–3800 mL), and the median duration of retention was 1200 minutes (range 470–10, 365 minutes). Fourteen patients performed intermittent self-catheterisation (ISC), six requiring this temporarily. No statistically significant association was demonstrated between retention characteristics and long-term functional outcomes of the bladder. Conclusions: This case series demonstrates cystodistension injuries to be unpredictable in their long-term impact. No association between volume and duration of retention and long-term bladder function was found. In the long term, 50% void spontaneously, 33% void spontaneously but require ISC to effect complete bladder emptying and 17% remain catheter dependent. Level of evidence: Level 4